2001
DOI: 10.1086/501929
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Staphylococcus aureus and of Gram-Negative Bacilli Resistant to Third-Generation Cephalosporins in Cirrhotic Patients A Prospective Assessment of Hospital-Acquired Infections

Abstract: Carriage of CephR strains is not associated with subsequent infection by these organisms in hospitalized cirrhotic patients. In contrast, MRSA carriage was an important risk factor for MRSA bacteremia and urinary tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 26 publications
0
19
0
3
Order By: Relevance
“…48 In the only comparative study to assess the independent use of antiseptic body washes for elimination of endemic S. aureus colonization, little difference was found between intra-nasal and wound mupirocin alone and mupirocin accompanied by chlorhexidine body washes, but this was an inadequately powered, non-randomized study. 68 Prevention of infection in a colonized patient Nasal decolonization S. aureus nasal carriage is a risk factor for subsequent infection, such as bacteraemia 23 and surgical-site infections (SSI), including cardiac 22 and orthopaedic surgery, 69 in patients with cirrhosis 70,71 and with HIV infection, 72 and in liver transplant recipients, 73 intensive care unit patients, 21,29,74 patients undergoing chronic ambulatory peritoneal dialysis (CAPD) 75 and haemodialysis patients. 76 It would seem reasonable to contend that eradication of nasal carriage would prevent infections with S. aureus, but the published randomized, controlled trials do not support this.…”
Section: Reduction In the Pool Of Mrsa Colonized Patientsmentioning
confidence: 99%
“…48 In the only comparative study to assess the independent use of antiseptic body washes for elimination of endemic S. aureus colonization, little difference was found between intra-nasal and wound mupirocin alone and mupirocin accompanied by chlorhexidine body washes, but this was an inadequately powered, non-randomized study. 68 Prevention of infection in a colonized patient Nasal decolonization S. aureus nasal carriage is a risk factor for subsequent infection, such as bacteraemia 23 and surgical-site infections (SSI), including cardiac 22 and orthopaedic surgery, 69 in patients with cirrhosis 70,71 and with HIV infection, 72 and in liver transplant recipients, 73 intensive care unit patients, 21,29,74 patients undergoing chronic ambulatory peritoneal dialysis (CAPD) 75 and haemodialysis patients. 76 It would seem reasonable to contend that eradication of nasal carriage would prevent infections with S. aureus, but the published randomized, controlled trials do not support this.…”
Section: Reduction In the Pool Of Mrsa Colonized Patientsmentioning
confidence: 99%
“…Cirrhosis of the liver is often associated with systemic endotoxaemia in the absence of sepsis [9][10][11], with the degree of endotoxaemia paralleling the degree of hepatic decompensation [12]. This was the basis for the Vallance and Moncada [8] hypothesis suggesting that the splanchnic/systemic endotoxin load could be the trigger for activating NOS activity with subsequent excess NO production.…”
Section: Endotoxaemia In Cirrhosismentioning
confidence: 99%
“…The nasal carriage of Staph. aureus is common, 20-50 % of the population (Cespedes et al, 2005), but also intestinal carriage appears to be increased among hospitalized patients (Dupeyron et al, 2001;Ray et al, 2003;Rimland & Roberson, 1986;Squier et al, 2002) and infants (Lindberg et al, 2000). Lindberg et al (2000) showed that over 75 % of Swedish infants have Staph.…”
Section: Introductionmentioning
confidence: 99%